Real Exchange Rates, Saving And Growth : Is There A Link? - Montiel, Peter, 1951- 1951- (The World Bank, 2008)
The view that policies directed at the real exchange rate can have an important effect on economic growth has been gaining adherents in recent years. Unlike the traditional "misalignment" view that temporary departures of the real exchange rate from its equilibrium level harm growth by distorting a key relative price in the economy, the recent literature stresses the growth effects of the equilibrium real exchange rate itself, with the claim being that a depreciated equilibrium real exchange rate promotes economic growth. While there is no consensus on the precise channels through which this effect is generated, an increasingly common view in policy circles points to saving as the channel of transmission, with the claim that a depreciated real exchange rate raises the domestic saving rate -- which in turn stimulates growth by increasing the rate of capital accumulation. This paper offers a preliminary exploration of this claim. Drawing from standard analytical models, stylized facts on saving and real exchange rates, and existing empirical research on saving determinants, the paper assesses the link between the real exchange rate and saving. Overall, the conclusion is that saving is unlikely to provide the mechanism through which the real exchange rate affects growth